If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-5-2x=3(x-2)+1
We move all terms to the left:
5x-5-2x-(3(x-2)+1)=0
We add all the numbers together, and all the variables
3x-(3(x-2)+1)-5=0
We calculate terms in parentheses: -(3(x-2)+1), so:We get rid of parentheses
3(x-2)+1
We multiply parentheses
3x-6+1
We add all the numbers together, and all the variables
3x-5
Back to the equation:
-(3x-5)
3x-3x+5-5=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| (3x-1)/2=5x-11 | | 11w-3w=64 | | 19=-4(r+5)+r | | 201=15+5d÷11 | | 3(x4)+12=9 | | 7^(x-5)=6 | | Y/5-1/2(y/2)=7/20 | | 27=2y-9 | | -(1×+7x)-6(-7-x)=36 | | 3(x+4)+4+12=9 | | x^2+20000*x+100009500=0 | | -103=-7+(-4x-14) | | 2x-3/4=x/3+1 | | Y=4/5x-7 | | 3x+36=7x+8 | | 6x+12(5000-x)=48000 | | -2+8(3x-5)=-162 | | (x+5)^2=13 | | 144=-3x+2(-7+21) | | Y=3x(-2)-6 | | -5(1-5x)+5(8x-2)=-4-8 | | 65=4x+3 | | -20=7x-5(4x-22) | | x(10x-2)=11 | | (3x-1)/3=0 | | 4(x-3)+6=-6 | | x2+25=125 | | 4x+2(3x+13)=-64 | | 8.1-1.8h=-7.2 | | Z=8+2i | | X+x+20+2(x+20)=180 | | x(x^2-12x)+192=0 |